The Legal Framework for Academic Professional Development for Radiographers in Higher Education - Žunić, Ljubica (Medicine, Law & Society, 2019)
Technology has changed the world of radiography, setting the request for development and promotion of radiography occupation. This article focuses on key factors of education for radiologic technologist / radiographer. The important role of EFRS in promoting and developing advanced educational standards and qualifications for radiographers is elaborated. Harmonization and development of radiographer’s profession following technological development considers cooperation among educational institutions, employers and professional bodies, within the framework of European and national legislation. Society should provide the conditions for further education. Obtaining a master's and / or doctoral degree, and integration in teaching and research activities, helps transform radiographers into leadership roles within their departments.
Keywords: Radiologic Technologist / Radiographer; Learning Outcomes; Standard of Qualification; Education